Penerapan Model PBL untuk Meningkatkan Kemampuan Menulis Teks Eksplanasi Siswa Kelas XI MIA-1 SMA Negeri 14 Maluku Tengah - Everhard Markiano Solissa (Universitas Muhammadiyah Surabaya, 2021)
The PBL Model Implementation to Improve Explanation Text Writing Ability Students of Class XI MIA-1 SMA Negeri 14 Maluku Tengah ABSTRAKPenelitian ini bertujuan meningkatkan kemampuan menulis teks eksplanasi siswa kelas XI MIA-1 SMA Negeri 14 Maluku Tengah. Data penelitian berupa hasil tes menulis teks eksplanasi setiap siklus. Subjek penelitian adalah siswa kelas XI MIA-1 SMA Negeri 14 Maluku Tengah tahun pelajaran 2020/2021 semester genap yang berjumlah 36 siswa. Nilai akhir setiap siswa diperoleh dari jumlah jawaban benar dibagi jumlah soal kemudian dikalikan dengan skor ideal (100). Nilai akhir tersebut kemudian dikonversikan sesuai kriteria yang ditentukan. Hasil penelitian menunjukkan bahwa terjadi peningkatan kemampuan menulis teks eksplanasi siswa kelas XI MIA-1 SMA Negeri 14 Maluku Tengah dengan menggunakan model pembelajaran problem based learning. Hal itu terlihat dari jumlah siswa yang mencapai KKM pada siklus I yakni 16 siswa menjadi 28 siswa pada siklus II. Kata kunci: kemampuan menulis, model pembelajaran problem based learning, PTK, teks eksplanasi. ABSTRACTThe aim of this study is to improve the ability to write explanatory texts for students of class XI MIA-1 SMA Negeri 14 Maluku Tengah. The research data were in the form of test results in writing explanatory text each cycle. The research subjects were students of class XI MIA-1 SMA Negeri 14 Maluku Tengah in the academic year 2020/2021 even semester, totaling 36 students. The final score for each student is obtained from the number of correct answers divided by the number of questions then multiplied by the ideal score (100). The final score is then converted according to the specified criteria. The results showed that there was an increase in the writing explanatory text ability for class XI MIA-1 SMA Negeri 14 Maluku Tengah using the problem based learning model. This can be seen from the number of students who reached the KKM (minimum standard of completeness in achieving learning result) in cycle I, namely 16 students to 28 students in cycle II.Keyword: writing skills, problem based learning model, PTK (Action research), explanatory text.